Where Beta Going - Case in Viet Nam Commercial Electric Industry During Post-Low Inflation Period 2015-2017 - Tuan Anh, Pham; Tran Ngoc Huy, Dinh; Thi My Phuong, Le; Minh Lan, Luong; Thi Phuong Thanh, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
The Vietnamese economy and commercial electric industry have gained lots of achievements after the financial crisis of 2007-2011, until they reached a low inflation rate of 0.6% in 2015. Software companies face challenges in expanding the Vietnam market, such as pricing policy and supporting services, etc. This paper measures the volatility of market risk in the Vietnamese electric industry after this period (2015-2017). The main reason is the vital role of the software company group in Vietnam in the economic development and growth in recent years, which always goes with risk potential and risk control policies. This research paper aims to figure out how much increase or decrease in the market risk of Vietnamese commercial electric firms during the post-low inflation period of 2015-2017. First, by using a quantitative combined with a comparative data analysis method, we find out the risk level measured by equity beta mean in the commercial electric industry is acceptable, i.e., it is a little lower than (